Effect of the coronavirus disease 2019 pandemic on pediatric emergency department visits for acute gastroenteritis evaluated using a validated clinical severity score - En-Shuo Chang; Pai-Jui Yeh; Chien-Chang Chen; Ming-Wei Lai; Hsun-Chin Chao; Hsin-Kuan Wu (Elsevier, 2023)
Background: The coronavirus disease 2019 (COVID-19) outbreak that began in late 2019 has significantly affected quality of life and healthcare. Approaches to prevent the spread of COVID-19 have also affected the prevalence of other diseases. This retrospective review evaluated pediatric emergency department (PED) volume, in terms of children with acute gastroenteritis (AGE), and changes in AGE severity before versus during the COVID-19 pandemic in a tertiary medical center in Taiwan. Methods: Patients who visited the PED and were diagnosed with AGE during the 70-day COVID-19 lockdown in 2021, or the identical period in 2020, were compared using a clinically validated AGE severity score, the modified Vesikari score (MVS), and additional parameters. Results: During the COVID-19 outbreak, there was a 61.4% reduction in the number of children with AGE visiting the PED. In that period, the AGE severity score was similar compared to the pre-pandemic period (9.00 vs. 8.57, p = 0.273). The mean C-reactive protein (CRP) level (55.7 vs. 40.6 mg/L, p < 0.001) and rate of antibiotics use (48% vs. 23.5%, p < 0.001) were higher during the outbreak than the pre-pandemic period. Conclusion: The number of children with AGE visiting the PED decreased during the COVID-19 outbreak, while disease severity was unchanged compared to the pre-pandemic period. The use of antibiotics during the COVID-19 pandemic warrants further investigation.